Diosmin attenuates paracetamol-induced hepato- and nephrotoxicity via inhibition of CY2E1-mediated metabolism in rats - Ravindra Babu Pingili, Sridhar Vemulapalli, Uday Bhaskar Narra, Sree Varsha Potluri, Naveen Babu Kilaru (Journal of Applied Pharmaceutical Science, 2023)
Cytochrome P-450 2E1 (CYP2E1) is responsible for forming a toxic metabolite N-acetyl-p-benzoquinoneimine (NAPQI) of paracetamol. In this study, we investigated the effect of diosmin, a flavonoid on the CYP2E1-mediated metabolism of paracetamol and NAPQI formation in Wistar rats. For 28 days, animals were orally administered with paracetamol (300 mg/kg) with and without diosmin (25 and 50 mg/kg). The blood samples were collected on the 28th day and the plasma concentrations of paracetamol and NAPQI were determined using the reverse phase high-pressure liquid chromatography. Paracetamol combination with diosmin (25 and 50 mg/kg) showed a dose-dependent increase in the area under the plasma concentration-time curve (AUC0–∞)and the peak plasma concentration (Cmax) of paracetamol and a dose-dependent decrease of AUC0–∞ and Cmax of NAPQI compared to paracetamol control (p < 0.001). Simultaneously, serum biomarkers and histopathological studies were conducted to evaluate the effect of diosmin on the liver and kidneys. Interestingly, compared to the paracetamol control group, the combination with diosmin significantly reduced the elevated functional biomarkers of liver and kidney. In addition, diosmin ameliorated paracetamol-induced hepatotoxicity and nephrotoxicity. The current study results revealed that diosmin showed a significant hepato- and nephroprotective activity by decreasing the formation of NAPQ1 through the inhibition of CYP2E1- mediated metabolism of paracetamol.
Keywords: CYP2E1, N-acetyl-pbenzoquinoneimine, diosmin, paracetamol, hepatotoxicity, nephrotoxicity